PENYULUHAN HUKUM TENTANG PENERTIBAN KAWASAN TELANTAR DAN TANAH TELANTAR - Lumme , Andreas (Batara Wisnu : Indonesian Journal of Community Services, 2025)
The state has been granted the land rights to the entitled party to be cultivated, used, utilized, and maintained properly. This is not only aimed at the welfare of the entitled party but also for the welfare of the community, nation, and state. The state has always granted the rights to the individual or legal entity, alongside with the obligations. However, inevitably abandoned areas and land are often found. Therefore, the counsel on abandoned areas and land is needed. This activity aims to increase government control and public awareness of preventing the occurrence of abandoned places and land. Abandoned areas are non-forest areas that have not been attached to the land rights that have permits/concessions/business permits, which are intentionally not cultivated, not used, and/or not utilized. Abandoned land is land rights, land management rights, and land obtained based on land control, which are intentionally not cultivated, not used, not utilized, and/or not maintained. Individual or legal entities who have obtained land rights or land control are obliged to maintain their land, cultivate it properly, and not abandon it. If they have ever left their land, the legal bond with the land will be abolished and soon will be confirmed as the land that directly controlled by the state. This outreach has motivated and increased awareness of the local community about the importance of effective land use and the importance of implementing abandoned areas and land regulations.